2019
DOI: 10.1101/773697
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A system for tracking whisker kinematics and whisker shape in three dimensions

Abstract: 25Quantification of behaviour is essential for systems neuroscience. Since the whisker system is a major model system for 26 investigating the neural basis of behaviour, it is important to have methods for measuring whisker movements from 27 behaving animals. Here, we developed a high-speed imaging system that measures whisker movements simultaneously 28 from two vantage points. We developed an algorithm that uses the 'stereo' video data to track multiple whiskers by 29 fitting 3D curves to the basal section o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 34 publications
1
22
0
Order By: Relevance
“…Other studies have approximated whiskers as quadratic curves (Quist & Hartmann, 2012; Towal et al, 2011), which cannot replicate inflections in curvature, or otherwise used cubic splines to capture whisker shape (Bagdasarian et al, 2013; Belli, Bresee, Graff, & Hartmann, 2018), but these are challenging to compare with one another. It is also possible to compare whisker outlines fitted with Elliptic Fourier harmonic coefficients (Ginter et al, 2012) or Bezier curves (Campagner, Evans, Loft, & Petersen, 2018; Hewitt et al, 2018; Petersen, Colins, Evans, Campagner, & Loft, 2020); although these are good visual representations of whisker shape, they do not provide a clear and succinct equation, which is useful for developing mechanical models. Therefore, as previously observed in rats (Starostin et al, 2020), we propose that a two parameter, linear curvature function (Equation ) provides a good approximation for whisker curvature.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have approximated whiskers as quadratic curves (Quist & Hartmann, 2012; Towal et al, 2011), which cannot replicate inflections in curvature, or otherwise used cubic splines to capture whisker shape (Bagdasarian et al, 2013; Belli, Bresee, Graff, & Hartmann, 2018), but these are challenging to compare with one another. It is also possible to compare whisker outlines fitted with Elliptic Fourier harmonic coefficients (Ginter et al, 2012) or Bezier curves (Campagner, Evans, Loft, & Petersen, 2018; Hewitt et al, 2018; Petersen, Colins, Evans, Campagner, & Loft, 2020); although these are good visual representations of whisker shape, they do not provide a clear and succinct equation, which is useful for developing mechanical models. Therefore, as previously observed in rats (Starostin et al, 2020), we propose that a two parameter, linear curvature function (Equation ) provides a good approximation for whisker curvature.…”
Section: Discussionmentioning
confidence: 99%
“…Such reconstructions have been first developed for constrained situations (e.g., treadmill walk) and by applying physical markers to detect body landmarks [ 25 ]. More recently, machine learning [ 26 , 27 , 28 ] and deep learning [ 29 , 30 , 31 ] have allowed to obviate for the need to use physical markers. Alternative approaches have also been taken by using depth cameras [ 32 ] or by combining traditional video with head-mounted sensors to measure head movements [ 33 ] and even eye movements and pupil constriction [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the last 20 years, multiple research groups have reported increasingly sophisticated, easy-to-use tools for automated annotation of video data of animal behavior (Knutsen et al, 2005;Voigts et al, 2008;Perkon et al, 2011;Clack et al, 2012;Ohayon et al, 2013;Giovannucci et al, 2018;Dominiak et al, 2019;Vanzella et al, 2019;Betting et al, 2020;Petersen et al, 2020). One natural extension of this ability has been to apply these algorithms for on-line, closed-loop paradigms, where changes in behavior of the animal are detected as rapidly as possible, and the behavior is used to modify or manipulate the brain, the virtual environment or the context of behavior.…”
Section: Challenges Towards Real-time Multi-whisker Detectionmentioning
confidence: 99%
“…Traditionally, video data have been analyzed manually. More recently, various algorithms have been developed for automating movement detection (Knutsen et al, 2005;Voigts et al, 2008;Perkon et al, 2011;Clack et al, 2012;Ohayon et al, 2013;Giovannucci et al, 2018;Dominiak et al, 2019;Vanzella et al, 2019;Betting et al, 2020;Petersen et al, 2020). With the development of DeepLabCut, a marker-less pose-estimation toolkit based on deep learning , computer vision approaches are being used for monitoring poses of animals and for tracking the movement of virtually any part of the body.…”
Section: Introductionmentioning
confidence: 99%